High mobility group box 1 and markers of oxidative stress in human cord blood - D'Angelo, Gabriella; Granese, Roberta; Marseglia, Lucia; Impellizzeri, Pietro; Alibrandi, Angela; Palmara, Antonella; La Rosa, Maria Angela; Manti, Sara; Salpietro, Carmelo; Spina, Edoardo; Reiter, Russel J; Falsaperla, Raffaele; et al. (Pediatrics international, 2019)
Background Parturition induces considerable oxidative stress and many inflammatory mediators, such as high mobility group box 1 (HMGB1), are involved from the beginning of the pregnancy to birth. The aim of the present study was to evaluate serum cord blood concentration of diacron‐reactive oxygen metabolites (d‐ROM), biological antioxidant potential (BAP), and HMGB1 to investigate the perinatal oxidative status of neonates and correlation with mode of delivery, as well as the influence of labor. Methods The subjects consisted of 214 neonates delivered at University Hospital “G. Martino”, Messina, in a 6 months period. Venous blood samples were collected from the umbilical cord after cord separation. Results Umbilical cord venous blood HMGB1 was significantly higher in the spontaneous vaginal delivery (SVD) group than in the elective or emergency cesarean section (CS) group (P = 0.018). Regarding labor, there was no significant difference in HMGB1 concentration in umbilical vein blood between the spontaneous and induced labor groups (P = 0.250). Furthermore, d‐ROM was significantly different between the SVD group and the elective or emergency CS group (P = 0.044). BAP concentration, however, was not significantly different, not even with regard to mode of labor. Conclusion Oxidation is higher in newborns delivered by SVD than in those delivered by CS, and HMGB1 may be involved in the mechanisms of birth, and responsible for decidual modifications that lead to birth.